Has underweight increased among children and adolescents during 2012–2019, and does the prevalence depend on socioeconomic circumstances? A nationwide register-based study from Denmark - Katrine Strandberg-Larsen; Lau C Thygesen; Anne Vedelsdal Aurup; Marie Borring Klitgaard; Anne Thorsted; Camilla Trab Damsgaard (BMJ Public Health, 2025)
Background Childhood underweight, indicated by low body mass index (BMI) for age and sex, is associated with morbidity, mortality and poverty in low-income settings, but is often overlooked in high-income countries, due to unequivocal focus on overweight. This study examined the prevalence and socioeconomic characteristics of underweight among children and adolescents in Denmark during 2012–2019.Methods We used nationwide Danish register data on height and weight measured objectively in 4 61 041 6–7 year-olds and 3 65 312 14–15 year-olds during 2012–2019, covering 89.4% and 67.2% of all schoolchildren in these age groups. We calculated BMI z-scores and classified underweight using the International Obesity Task Force age- and sex-specific BMI cut-offs and linked with data on parental education and household income as indicators of socioeconomic circumstances.Results The prevalence of underweight remained relatively stable at~8.5% among 6–7-year-old girls during 2012–2019. Among 14–15-year-old girls, it was initially higher but decreased slightly (<1%-point) to 8.6% in 2019. Among boys, the prevalence increased from ~7% to just above 8% in both age groups during the period. Across all years, underweight was more common among 14–15 year-olds whose parents had long higher education (girls: 10.4%–12.1%; boys: 8.7%–10.2%) compared with primary school (girls: 5.6%–7.5%; boys: 6.1%–7.8%), with the most pronounced differences among girls. Similar differences across parental education were observed among 6–7 year-olds, although they were smaller. Less distinct but comparable differences in underweight prevalence were found across household income.Conclusions Underweight is prevalent but has remained relatively stable during the 2010s among Danish children and adolescents. Unlike the pattern reported in low-income settings, and that seen for overweight, underweight is associated with socioeconomic advantage in this high-income setting.